Justice for trans athletes : challenges and struggles - Greey, Ali Durham; Lenskyj, Helen (Emerald studies in sport and gender, 2022)
The last decade has seen significant changes in global attitudes, policies and practices that impact the lives of trans people, but the world of sport has been slow to follow these initiatives. Contributors to this book document the formidable social-cultural and legal challenges facing trans athletes, particularly girls and women, at the global, national, and local levels, in contexts ranging from school sport to international competition. They demonstrate how proponents of trans exclusion rely on flawed or inconclusive science, selectively employed to support their purported goal of 'protecting women's sport'. Politicians in the US, UK, and elsewhere who have shown little interest in women or in sport exploit the issue to advance broader conservative agendas, while hostile mainstream and social media coverage exacerbates the problem. Bringing insights from sociology, philosophy, science and law, contributors present cogent analyses of these developments and explore the way forward, providing thoughtful and original recommendations for changes to policies and practices that are inclusive, innovative and democratic.